BUILDING SCALABLE AI-DRIVEN MDM STRATEGIES WITH D365: A TECHNICAL DEEP DIVE - Babita Kumari (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article examines the implementation of Artificial Intelligence (AI) in Master Data Management (MDM) within Microsoft Dynamics 365 (D365) environments. As organizations grapple with managing an average of 347.56 terabytes of data across 400+ applications, traditional MDM approaches have become unsustainable. The article demonstrates how AI-driven MDM solutions achieve significant improvements in data quality, operational efficiency, and cost reduction. Through comprehensive analysis of enterprise implementations, the article reveals that organizations achieve a 78% reduction in data processing time and a 92% improvement in data quality metrics. Key technological components include advanced data matching engines achieving 98.5% accuracy, anomaly detection systems processing 750TB daily, and NLP pipelines supporting 95% of global business languages. The implementation framework incorporates microservices architecture, achieving 99.99% uptime and real-time data synchronization across global operations. Case studies demonstrate substantial financial benefits, including annual savings of 1.5 million and 60% reduction in resource utilization. The article provides a structured approach to implementation, covering model training strategies, governance frameworks, and future developments in quantum computing and federated learning integration.